PENYULUHAN AGAMA DAN PRODUKTIVITAS MASYARAKAT - M. Kholili; Syamsul Hadi; Subejo Subejo (Universitas Muhammadiyah Sidoarjo, 2015)
Dakwah is communication teachings of Islam to mankind which is established communication process. This communication process is done by a preacher called religious counselors. Religious counselors must be able to communicate, so the counselors capable and skilled to empathize and interact with the mankind. The purpose of dakwah can be delivering well. In this article, communication and counseling science will be used as a knife of communication activities analysis and counseling of Islam religion. The authors hope to obtain findings that will assist in designing the implementation of dakwah in the future so that dakwah will take place better, effective and efficient.